(untitled) (The Pakistan Development Review, 2025)
The study provides a socio-economic analysis of the street economy using primary data based on a survey of 1,863 fixed street vendors operating in the Twin Cities of Pakistan. Descriptive analysis shows that street vendors, on average, make a significant profit of US 212 per month (29 percent of total monthly revenue). They chose to vend due to the lack of formal education and the unavailability of formal sector jobs. Vendors pay more than 51 percent of their operating cost (US107 per month) as rent to shop owners to place carts/tables in front of shops. About 98 percent of vendors operate without legal protection (e.g. license/permit), leading to frequent evictions. The economic loss constitutes about 62 percent of the monthly revenue (215 percent of the monthly net profit) due to one-time expulsion by the administration. The Multidimensional Vulnerability Index (MVI) shows that around 21 percent of vendors are acutely vulnerable, while more than 25 percent of SVs are vulnerable. Multivariate analysis indicates that socio-economic vulnerabilities negatively and significantly impact monthly profits. These findings provide insights to policymakers and other stakeholders, including entrepreneurs, market associations, regulators, administrative authorities, and social protection agencies, to harness the potential economic benefits of the street economy.